Avaliação da memória de longo prazo em idosos nas condições háptica e visual - Ferreira, Cyntia Diógenes (2015)
The ratings used for the memory studies may vary from the nature of the encoding of stimuli, as to the time when the information remains stored for later retrieval and as the form of engaged learning. Thus, studies that evaluate the coded memory through active manipulation of objects, the haptic memory, are scarce, in particular the assessment of long-term oblivion rates. In the healthy aging process subsystems memory have different significant decline in its components. Therefore, the present study aimed to evaluate the real objects oblivion rates and family processed in the haptic and visual modality in two time slots to recall memories and recognition in a sample of 104 elderly people, of both sexes, without commitment cognitive. For this, a wooden box and a turntable for the presentation of haptic and visual stimuli, respectively were used. The procedure consisted of two phases, one phase of study (stimulus presentation) and another test (recall or recognition tasks), at intervals of 1 hour or 1 day. The Mann-Whitney test for independent samples showed significant differences in the recall task only at 1 day interval, with a superior visual recall of information (U = 55.50, p = 0.029, r =-0,60). In the assessment of the accuracy of recognition revealed that only 1 day interval was no significant difference, however, by superior to haptic condition (U = 55.50, p = 0.029, r =-0,55). In summary, the results show that for different memory tasks evaluation condition influences the forgetting rates over time. So it is necessary that new designs, with the addition of more extended periods of time, may bring further clarification.